Seven Steps of Interreligious Dialogue of Action Increasing Employee's Engagement - Kanisius Komsiah Dadi; Theresia Maria Margi Jatining Kasih (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
The present study aims to identify an effective way of promoting employee engagement through interfaith dialogue. The research employed a descriptive qualitative approach, and the sample consisted of Atma Jaya Catholic University of Indonesia employees. As a Catholic institution, Atma Jaya is committed to the values of the Christian faith and Pancasila (Tuhan dan Tanah Air), which reflect Indonesia's diverse cultural and religious landscape. The university's founders envisioned an academic community embodying Christian faith, excellence, professionalism, and care (Kristiani, Unggul, Profesional, Peduli-KUPP). However, building these values in every community member has proven to be a challenge, as evidenced by the low level of employee engagement.Employee engagement is an essential factor in promoting individual well-being and organizational success. It refers to the positive, fulfilling, and meaningful involvement in work activities characterized by dedication, enthusiasm, and absorption. Work plays a critical role in societal development, as it contributes to advancing various fields and providing goods and services. In this regard, Atma Jaya can leverage dialogical approaches to enhance the quality of social life in society. The university has adopted a strategy for promoting dialogue among individuals from diverse ethnic, religious, and cultural backgrounds, known as "Refleksi Karya." This approach involves seven steps of dialogue of action, emphasizing the view that work is a manifestation of faith in God.Faith is a strong belief in the doctrines or teachings of a particular religion. A pluralistic society refers to the practice of religious or spiritual beliefs within a community characterized by diversity in religious, cultural, and philosophical perspectives. Promoting open and constructive communication between religious groups fosters understanding, reduces misconceptions, and promotes cooperation among people with diverse beliefs. The ultimate objective is to achieve social harmony, where individuals of different faiths can coexist peacefully, collaborate for the common good, and contribute positively to the community's and society's overall well-being. Atma Jaya's "Refleksi Karya" approach invites individuals to reflect on their responsibilities through seven steps of dialogue of action, including looping, awareness building, sharing, teaching, reflecting, confirming, and doing.